PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Safitri, Ade Ayu; Rosyati, Tati (Publika Citra Media, 2024)
This research aims to test and obtain empirical evidence regarding the influence of Managerial Ownership, Company Size, and Corporate Social Responsibility on Company Value. The population in this research is transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample used in this research was 10 companies with a research observation period of 5 years in the 2018-2022 period and the number of financial reports sampled in this research was 50 pieces of data. The analysis technique used in this research is panel data regression on Eviews 9 Software. The results of this research show that simultaneously Managerial Ownership, Company Size, and Corporate Social Responsibility together have a significant effect on Company Value. Partially, company size has a significant negative effect on company value, while managerial ownership and corporate social responsibility do not have a significant effect on company value.